APPLICATION OF THE PRINCIPLE OF PROPORTIONALITY BY THE POLICE IN HANDLING CRIMES - Darise, Zulkarnain; Robby Waluyo Amu; Ramdhan Kasim (Judge : Jurnal Hukum, 2026)
This study examines the formal education requirements for Assistant Investigators in Government Regulation (GR) No. 58 of 2010 concerning Amendments to GR No. 27 of 1983 concerning the Implementation of the Criminal Procedure Code (KUHAP) and formulates strategies for strengthening formal education to improve the quality of human resources (HR) in the Indonesian National Police's Criminal Investigation Unit. The background of this study stems from the strategic role of the Indonesian National Police in the criminal justice system and the increasing complexity of modern crimes that demand higher legal and technical competence. The research questions include: (1) how is formal education regulated for assistant investigators in PP 58/2010; and (2) what are the strategies for strengthening formal education to improve the quality of the Indonesian National Police's human resources. This study uses a normative legal research method with a descriptive-analytical nature, based on primary legal materials (1945 Constitution, Criminal Procedure Code, Law No. 2 of 2002, PP 58/2010, related Perkap), secondary legal materials (books, journals, previous studies), and tertiary legal materials (dictionaries, encyclopaedias, regulation indexes), which were collected through literature studies and analysed qualitatively through a legislative, conceptual, and historical approach. The results of the study show that PP 58/2010 only emphasises technical education and training as well as work experience for assistant investigators without requiring a minimum formal education of a bachelor's degree, thus creating a competency gap compared to lead investigators and potentially reducing the quality and legitimacy of investigations. In the field, some work units have required a bachelor's degree and provided scholarships and distance learning programmes, but implementation has been uneven due to constraints in access, budget, and infrastructure. This study recommends regulatory reform by setting a minimum education standard of a bachelor's degree for assistant investigators, strengthening police education institutions (e.g. through police universities), expanding scholarships and online education, partnerships with universities, and a competency-based career development and certification system to strengthen the professionalism and accountability of the Indonesian National Police's human resources.